ACTIVE LEARNING STRATEGIES INCREASING MOTIVATION TO LEARN ISLAMIC RELIGIOUS AT THE PRIMARY SCHOOL (SDIT) INSAN RABBANI LAMPUNG - Izzah Azizah AlHadi; Maya Setia Priyadi; Mela Suhariyanti (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2023)
Motivation for learning is needed to generate enthusiasm for learning and acquiring knowledge. This research method is qualitative through observation, interviews, and documentation. This research was conducted at Primary School IT Insan Rabbani Kotabumi, North Lampung. This study aims to discover that the application of active learning strategies in learning Islamic religious education can significantly impact learning Islamic religious education. The results obtained in this study are that the Primary School IT Insan Rabbani uses various learning methods in the learning process because that way, students have the motivation to study religion and are motivated to be active in learning, The learning methods used are such as Snowball Throwing, making creations, being present in front of the class, singing, and asking questions. Learn with various methods so that students are active and motivated to study Islamic religious education, and, in this way, students can more easily understand and remember Islamic religious education lessons. Abstrak: Motivasi dalam pembelajaran sangat dibutuhkan untuk membangkitkan semangat belajar dalam memperoleh ilmu pengetahuan. Metode penelitian ini ialah kualitatif dengan melalui observasi, wawancara dan dokumentasi. Penelitian ini dilakukan di SDIT Insan Rabbani Kotabumi Lampung Utara. Penelitian ini bertujuan untuk mengetahui bahwa penerapan strategi pembelajaran aktif dalam pembelajaran Pendidikan agama islam dapat memberikan dampak yang besar pada pembelajaran Pendidikan agama islam. Hasil yang diperoleh dalam penelitian ini ialah SDIT Insan Rabbani menggunakan berbagai macam metode pembelajaran dalam proses pembelajaran karena dengan begitu siswa memiliki motivasi untuk belajar ilmu agama, dan termotivasi untuk aktif dalam pembelajaran, metode pembelajaran yang digunakan yaitu seperti: ‘Snowball Throwing’, membuat kreasi kemudian di presentasikan di depan kelas, menyanyi dan tanya jawab. Membuat pembelajaran dengan berbagai macam metode agar siswa aktif dan memiliki motivasi untuk belajar Pendidikan agama islam dan dengan begini siswa jadi lebih mudah memahami dan mengingat pelajaran Pendidikan agama islam. Kata Kunci: Strategi Pembelajaran Aktif, Motivasi, Pendidikan Agama Islam.